2021
DOI: 10.9734/aprj/2021/v8i430188
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Indigenous Traditional Knowledge (ITK) on Commonly Available Plants in Koira Range, Bonai Forest Division, Sundargarh, Odisha, India

Abstract: Mining activities are an important source of revenue for the development of the nation. However, it creates lots of social and ecological imbalance. The major remarked problem is that the local communities of mining areas losses their Indigenous Traditional Practices. Keeping this in view, an attempt has been made to document the indigenous traditional knowledge on commonly available plants in Koira Range, a mining impacted areas of the Bonai Forest Division, Odisha, India. Twenty nine villages of 4 sections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In 2020, Das et al [33] reported the diversity of climbers in Odisha. Therefore, there is a need of further documentation on climbers in Odisha [34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Das et al [33] reported the diversity of climbers in Odisha. Therefore, there is a need of further documentation on climbers in Odisha [34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…The opinion was taken after discussion with experts in ResearchGate platform and mentioned in the Observations section. The interaction was carried out with indigenous communities of study areas and their opinion on forest fire and Rugda mushroom (Astraeus hygrometricus) collection was recorded and presented in the section of case study [4]. The collected data were analyzed to show that how forest fire is related to the lives of indigenous community of study areas.…”
Section: Methodsmentioning
confidence: 99%
“…Among the seven ranges, Koira, Barsuan and Kuliposh come under the mining-impacted areas. Koira and Barsuan ranges have unique bio-wealth [4].…”
Section: Study Areasmentioning
confidence: 99%
“…To learn more about wild edible mushrooms and their economic worth from vendors, villagers, and local communities, the authors travelled to several local markets, state highways, district roads, village roads, and tribal settlements. Utilizing the available literature, mushrooms are identified [6][7][8][9][10][11]. The local name(s) of enumerated wild mushrooms were noted and presented.…”
Section: Methodsmentioning
confidence: 99%